Scaling limit of virtual states of triatomic systems - Yamashita, Marcelo Takeshi [UNESP]; Frederico, T.; Delfino, A.; Tomio, Lauro [UNESP] (American Physical Society (APS), 2002)
Natural scales determine the physics of quantum few-body systems with short-range interactions. Thus, the scaling limit is found when the ratio between the scattering length and the interaction range tends to infinity, while the ratio between the physical scales are kept fixed. From the formal point of view, the relation of the scaling limit and the renormalization aspects of a few-body model with a zero-range interaction, through the derivation of subtracted three-body T-matrix equations that are renormalization-group invariant.
Keywords: Binding energy; Calculations; Functions; Ground state; Integral equations; Mathematical models; Molecular dynamics; Dirac interaction; Scaling limit; Three body model; Triatomic systems; Virtual state energy; Atomic physics